IMPROVEMENT OF MECHANISMS OF TRAINER-ATHLETE DYAD RELATIONS IN SPORTS SCHOOLS (Conferencea, 2023)
The expansion of the competition, the continuous increase in the number of applicants for the highest awards in the most prestigious international competitions, creates the need to search for new scientifically based methods and tools in the training system of highly qualified athletes. One of the ways to improve the effectiveness of this training is to develop optimal forms of interaction and relationships in the "coach-athlete" system. The study of the coach's and athlete's personality should have an individual character and reveal the main distinguishing features of both, where the level of development of the coach's personality must take the leading place in the structure of his activity. The higher this level, the stronger and more permanent the influence of the coach on the athlete.